Controlling of optical bistability and multistability via two different incoherent processes. (1st May 2023) - Saeed Mohammed, Murtadha; Subhi Ali, Ahmed; Mourad Mohammed, Ibrahim; Yasin, Yaser; Auda Abdulameer, Sabah; Salam Obaid, Zahraa; Hadrawi, Salema K
Abstract: In this paper, we investigate the optical bistability (OB) and optical multistability (OM) phenomena for a quantum dot nanostructure via two different mechanisms. The first process is based on the application of the incoherent pumping field while the second one is due to the ratio between the injection and cavity injection rates. We show that the appearance of OB and OM properties in the system depends strongly on the presence of these mechanisms. It is found that OB appears in the presence of both mechanisms, but OM appears only when both mechanisms are present in the system simultaneously. We also study the linear absorption behaviors for the case when OB and OM are observed in the system. It is shown that for the multistable state, the absorption properties of the system are different from the bistable state, which has a strong dependence on incoherent processes.